Regulation of megakaryo/thrombopoiesis by endosomal toll-like receptor 7 and 8 activation of CD34+ cells in a viral infection model - Rodríguez, Camila Sofía (2023)
Background: CD34+ cells, megakaryocytes (MKs), and platelets express toll-like receptors (TLRs) that enable these cells to amplify the host innate immune response. However, the role of TLR7/TLR8 activation in megakaryopoiesis has not yet been investigated. Objectives: We evaluated the effect of coxsackievirus B3 (CVB3) and synthetic TLR7/TLR8 agonists on the development of human MKs and production of platelets. Methods: CD34+ cells from human umbilical cord were inoculated with CVB3 or stimulated with synthetic TLR7/TLR8 agonists and then cultured in the presence of thrombopoietin. Results: CD34+ cells, MK progenitor cells, and mature MKs expressed TLR7 and TLR8, and exposure to CVB3 resulted in productive infection, as determined by the presence of viral infectious particles in culture supernatants. Cell expansion, differentiation into MKs, MK maturation, and platelet biogenesis were significantly reduced in CD34+-infected cultures. The reduction in MK growth was not due to an alteration in cellular proliferation but was accompanied by an increase in cellular apoptosis and pyroptosis. Impairment of MK generation and maturation of viable cells were also associated with decreased expression of transcription factors involved in these processes. These effects were completely abrogated by TLR7 but not TLR8 antagonists and mimicked by TLR7 but not TLR8 agonists. CVB3 infection of CD34+ cells increased the immunophenotype of MKs characterized as CD148+/CD48+ or CD41+/CD53+ cells. Conclusion: These data suggest a novel role of TLR7 in megakaryo/thrombopoiesis that may contribute to a better understanding of the molecular basis underlying thrombocytopenia and the immunologic role of MKs in viral infection processes.